Novel Object Recognition in Rats With NMDAR Dysfunction in CA1 After Stereotactic Injection of Anti-NMDAR Encephalitis Cerebrospinal Fluid - Kersten, Maxi; Rabbe, Theresa; Blome, Roman; Porath, Katrin; Sellmann, Tina; Bien, Christian G.; Köhling, Rüdiger; Kirschstein, Timo (Frontiers in Neurology, 2019)
Purpose: Limbic encephalitis associated with autoantibodies against N-methyl D-aspartate receptors (NMDARs) often presents with memory impairment. NMDARs are key targets for memory acquisition and retrieval, and have been mechanistically linked to its underlying process, synaptic plasticity. Clinically, memory deficits are largely compatible with a predominantly hippocampus-dependent phenotype, which, in rodents, is principally involved in spatial memory. Previous studies confirmed the impaired spatial memory in the rat model of anti-NMDAR encephalitis. Here, we hypothesized that nonspatial memory functions such as object recognition might also be affected in this model. Methods: We performed stereotactic intrahippocampal bolus injection of human cerebrospinal fluid (CSF) from anti-NMDAR encephalitis and control patients into the hippocampus of the anesthetized rat. After recovery for 1-8 days, hippocampal slices were prepared from these animals and NMDAR-dependent long-term potentiation was assessed at the Schaffer collateral-CA1 synapse. In addition, we performed behavioral analyses using the open field and novel object recognition tasks. Results: NMDAR-dependent long-term potentiation in the hippocampal CA1 area was significantly suppressed, indicating successful NMDAR dysfunction in this subfield. Spontaneous locomotor activity as well as anxiety-related behavior in the open field did not differ between NMDAR-CSF-treated and control animals. In the novel object recognition task, there were no differences in the motivation to approach objects. In contrast, we observed a significantly preferred exploration of the novel object only in control, but not in NMDAR-CSF-treated rats. Conclusion: These results indicate that NMDAR dysfunction obtained by intrahippocampal stereotactic injection does not alter locomotor or anxiety-related behavior. In addition, approach to an object or exploratory behavior in general are not affected either, but intact initial NMDAR-dependent processes might be involved in novel object recognition.